(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the article, the methodological basis of budget control in the process of public procurement and how it is related to state financial control was studied. In addition, state procurement was mainly analyzed. The problem of improving compliance of budgetary organizations and institutions financed from the budget with the budget and budget discipline is still relevant today.